THE FUNDAMENTAL POSTULATES OF JUSTICE, FAIRNESS AND CONSENSUAL DECISION-MAKING IN CRIMINAL PROCEEDINGS - Knežević, Saša; Trajković, Marko; Drakić, Dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
In criminal proceedings, the justification of the prosecutor’s criminal demand for punishing the accused is decided upon. The basic postulates of justice dictate that the human rights of the perpetrator of a criminal act can be restricted based on a conviction, which is the result of the conducted criminal procedure. The theory of criminal law, especially legislation, should find ways to bring justice from legal-philosophical heights into the reality of a conflicted society. Along with the standard methods of social reaction which, in the first place, is mandatory initiation of criminal proceedings whenever legal conditions are met, positive law also prescribes possibilities of consensual decision-making. The materialization of the concept of consensual justice is achieved in the pre-trial procedure as well as in the formal criminal procedure. By conditional postponement of criminal prosecution, the criminal matter finds its epilogue in the pre-trial procedure. Thus, no judicial decision is being made on the merits of the criminal demand, and the public prosecutor becomes some kind of adjudicator of the criminal matter. The concept of consensual justice is brought to life within criminal proceedings by party agreements – one of the forms of consensual decision-making. Different forms of this procedure contribute to the efficiency of the criminal procedure as well as the realization of criminal policy aims. Deciding on the guilt of the accused is simplified, and, on the other hand, the accused and the convicted, as collaborators of the court, facilitate the understanding of decisive facts about the criminal event with their statements.